2021
DOI: 10.3390/atmos12040480
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Spatiotemporal Analysis of Extreme Events in the Gomati River Basin, India

Abstract: Accelerating climate change is causing considerable changes in extreme events, leading to immense socioeconomic loss of life and property. In this study, we investigate the characteristics of extreme climate events at a regional scale to -understand these events’ propagation in the near future. We have considered sixteen extreme climate indices defined by the World Meteorological Organization’s Expert Team on Climate Change Detection and Indices from a long-term dataset (1951–2018) of 53 locations in Gomati Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The R/S method, as described in previous studies [38,[67][68][69][70], involves the following steps: Firstly, compute, respectively, the range R τ and standard deviation S τ using Equations ( 11) and ( 12)…”
Section: Rescaled Range (R/s) Analysismentioning
confidence: 99%
“…The R/S method, as described in previous studies [38,[67][68][69][70], involves the following steps: Firstly, compute, respectively, the range R τ and standard deviation S τ using Equations ( 11) and ( 12)…”
Section: Rescaled Range (R/s) Analysismentioning
confidence: 99%
“…Studies in analyzing precipitation trends have been reported across the world in various river basins such as the Indus basin [47], Vea catchment [48], Awash River basin [49], and Yarlung river basin [40]. Similarly, in India, trend studies using gridded satellite products have been performed in the Kosi River basin [50], the Cauvery basin [51][52][53], and the Gomati basin [54].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this study examines the precipitation concentration in the area based on data with daily resolution. The DPCI is also good supplementary information to other extreme precipitation indices on similar timescale, such as the highest amount of daily precipitation (RX), the maximum consecutive 5-day precipitation (RX5D), number of days with precipitation ≥ 20 mm or above 50 mm (R20/D50MM) and days with precipitation > 95 percentile (D95P) recommended by the World Climate Research Programme's Expert Team on Climate Change Detection and Indices (ETCCDI, [21,22]).…”
Section: Introductionmentioning
confidence: 99%